1999
DOI: 10.1159/000023374
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of the Aldosterone Synthase and Steroid 11β-Hydroxylase Deficiencies

Abstract: The most potent corticosteroids are 11β-hydroxylated compounds. In humans, two cytochrome P450 isoenzymes with 11β-hydroxylase activity, catalysing the biosynthesis of cortisol and aldosterone, are present in the adrenal cortex. CYP11B1, the gene encoding 11β-hydroxylase (P450c11), is expressed on high levels in the zona fasciculata and is regulated by ACTH. CYP11B2, the gene encoding aldosterone synthase (P450c11Aldo), is expressed in the zona glomerulosa under primary control of the renin-angiotensin system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 55 publications
0
41
0
1
Order By: Relevance
“…Therefore, the classical form of 11b-OHD, with an estimated frequency of 1:200 000 live births, is characterized by genital ambiguity in affected girls and postnatal hyperandrogenism in both sexes resulting in precocious pseudopuberty with rapid somatic growth, bone age acceleration and hypertension in about two-thirds of patients. 3,4 The milder nonclassical forms are very similar to the 21-OHD non-classical forms characterized by mild virilization and precocious pseudopuberty. 5,6 In these mild forms, whose frequency is unknown, hypertension does not occur often.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the classical form of 11b-OHD, with an estimated frequency of 1:200 000 live births, is characterized by genital ambiguity in affected girls and postnatal hyperandrogenism in both sexes resulting in precocious pseudopuberty with rapid somatic growth, bone age acceleration and hypertension in about two-thirds of patients. 3,4 The milder nonclassical forms are very similar to the 21-OHD non-classical forms characterized by mild virilization and precocious pseudopuberty. 5,6 In these mild forms, whose frequency is unknown, hypertension does not occur often.…”
Section: Introductionmentioning
confidence: 97%
“…These hormones are associated with a variety of physiological processes including metabolism, stress responses, immune responses, vasoconstriction, growth, development, salt and water homeostasis and vascular tone (Mommsen et al, 1999;Osborn, 1991). Studies have shown that decreased production of these hormones may impair normal physiological processes and cause pathologic effects in vivo (Peter et al, 1999;Ueshiba et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The mean ages and age ranges of women in PCOS, IH and CS groups were as follows: 24.71 ± 3.92 years (17-34), 22.19 ± 3.71 years (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 23.18 ± 4.50 years (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), respectively. None of the subjects in any group had received any hormonal medication at least eight weeks before the study.…”
Section: Methodsmentioning
confidence: 99%
“…There is no doubt that the main diagnostic evaluation should be based on molecular studies [16,17], but this may limit the uncovering of some cases since molecular studies are neither prevalent nor easy to do. On the other hand, while there is still an enigma about the diagnosis of LO CAH by using hormonal analysis, ACTH stimulation test still consists of the gold standard test for the evaluation of adrenal response and enzyme deficiencies causing LO CAH [18,19].…”
mentioning
confidence: 99%